2022
DOI: 10.55713/jmmm.v32i2.1259
|View full text |Cite
|
Sign up to set email alerts
|

DC Conductivity of Heavy Metal Oxide (Bi2O3) Boro-Tellurite Glasses: Effect of Eu2O3

Abstract: A novel investigation on structural and DC conductivity of Eu2O3 activated heavy metal oxide boro-tellurite (BBTE) glasses were analyzed. The boro-bismuth-tellurite glass samples doped with europium trioxide were fabricated by the conventional melt quenching method. The microstructural and structural studies of the glasses have been done by scanning electron microscope (SEM) and X-ray diffraction (XRD), respectively. The DC conductivity of the BBTE samples has been studied at the frequency range 40Hz-6MHz and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…The significant variations in the density are attributed to i) larger changes in average molecular weight in oxide ions of glass owing to the higher molecular weight of Eu2O3 than B2O3, ii) considerable changes in molar mass of europium trioxide, iii) addition of lead ions with Eu 3+ ions holds greater atomic mass. Additionally, the generation of nonbridging oxygen (NBO) in LABT glasses also impacts modifications in density, and similar work is also reported in the literature [1,9,11,20,[38][39][40][41]. It is noticed that the density of glasses has been increased up to LABT2 glasses with rise in concentration of Eu2O3 and decreased at LABT3 and LABT4 glasses.…”
Section: Physical Propertiessupporting
confidence: 69%
See 3 more Smart Citations
“…The significant variations in the density are attributed to i) larger changes in average molecular weight in oxide ions of glass owing to the higher molecular weight of Eu2O3 than B2O3, ii) considerable changes in molar mass of europium trioxide, iii) addition of lead ions with Eu 3+ ions holds greater atomic mass. Additionally, the generation of nonbridging oxygen (NBO) in LABT glasses also impacts modifications in density, and similar work is also reported in the literature [1,9,11,20,[38][39][40][41]. It is noticed that the density of glasses has been increased up to LABT2 glasses with rise in concentration of Eu2O3 and decreased at LABT3 and LABT4 glasses.…”
Section: Physical Propertiessupporting
confidence: 69%
“…It has been reported that direct and indirect bandgap data well fit an Equation (5) proposed by Davis and Mott. [1,9,18,20,21,[40][41][42][43][44][45][46].…”
Section: Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations